2020
DOI: 10.1002/cctc.202001319
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Simple Surface Treatments of N, P Dual‐doped Carbon as Metal‐free Catalyst for Metal‐air Batteries

Abstract: N, P dual‐doped porous carbon with high specific surface area of ∼2000 m2 g−1 was prepared via foaming‐carbonization process. It was demonstrated that the simple surface treatment and modification can conveniently further improve the catalytic performance of oxygen reduction reaction (ORR). The results showed that chemisorbed phosphorus can promote the surface treatment of sodium borohydride (NaBH4). The modified novel sites, adsorbing water molecules of a semi‐free state, promoted the offensive key steps of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Tafel plot is a linear plot that consists of the over potential (η) Vs current density (j) on a logarithmic scale as shown below Tafel Eq. : [39,40] trueη=normalb4ptlog4ptnormalj+normala …”
Section: Resultsmentioning
confidence: 99%
“…Tafel plot is a linear plot that consists of the over potential (η) Vs current density (j) on a logarithmic scale as shown below Tafel Eq. : [39,40] trueη=normalb4ptlog4ptnormalj+normala …”
Section: Resultsmentioning
confidence: 99%
“…Carbon materials (such as graphene, carbon nanotube, and porous carbon) are of great interest due to their inherent advantages. [50][51][52][53][54][55][56] Metal-free carbon-based electrocatalysts showed superior ORR performances in both acidic and alkaline electrolytes. [57][58][59] In addition, it has emerged as a promising electrocatalyst owing to its advantages such as earth abundance, low price, environmental friendliness, and ease in tunability of their catalytic properties and structures.…”
Section: Metal-free Electrocatalystsmentioning
confidence: 99%
“…To determine the practical application in energy devices for NHC-X, we used NHC-900 to construct a rechargeable zinc-air battery. [50] As shown in Figure 6a, polis zinc plate (0.1 mm thickness) was used as anode, 6.0 M KOH solution containing 0.2 M zinc acetate was electrolyte and NHC-900 loaded on the surface of gas diffusion layers was used as air cathode. [51,52] It was observed that the open circuit voltage (OCV) for NHC-900 catalyzed battery was 1.351 V by multi-meter (Figure 6b).…”
Section: Rechargeable Zinc-air Battery Testsmentioning
confidence: 99%